Super resolution and its application in microscopy images - Komal Agarwal. (2010)
Any imaging system captures a scene with only finite levels of resolution as compared to the actual scene. To increase the resolution of an imaging system, two solutions can be implemented - hardware or software. However, it is not always practical to achieve higher resolution by enhancing the hardware due to feasibility issues. Therefore, in such a situation, it is better to devise a software solution to improve the resolution of the images taken by the imaging system. One such solution is super-resolution imaging. Super-Resolution (SR) imaging is an image processing technique that aims to produce high quality, high-resolution (HR) images by utilizing a sequence of shifted low-resolution (LR) images. Most of the SR algorithms described in literature have applied this technique on regular images taken with a hand-held camera. In contrast, this project focuses on the application of super resolution on microscopic images of minute objects that are taken under poor optical conditions. The report describes an experiment that was carried out on a USAF target to test the effectiveness of the SR technique under non-ideal conditions. It was realized that the method was not as straight forward for microscopic images as it is for normal images, and many shortcomings have to be overcome to get good results. However, after resolving some of the limitations, super resolution proved to be quite effective on the acquired USAF images. The resultant SR images were definitely of higher quality and resolution as compared to the original LR images. Application of Super Resolution in the field of biomedicine is a relatively new area of research. Infact, it has not yet been implemented in Photo-thermal Imaging (PTI) systems that aim to provide a resolution exceeding the diffraction limit. In this project, Super resolution has been performed on acquired photo-thermal images of 5um Polystyrene beads. The results show significant improvement in the SR images as compared to the original photo-thermal images, mainly in terms of sharpness, clarity and resolution.